Clip or Tattooing: A Comparative Study for Preoperative Colon Cancer Endoscopic Localization - Zhang, Shengyu; Wang, Qiang; Feng, Yunlu; Zhang, Guannan; Chen, Yang; Zheng, Weiyang; Wu, Xi; Yang, Aiming (Frontiers in Oncology, 2022)
Background and aim: Preoperative endoscopic markers have been extensively used for the localization of colonic neoplastic lesions in laparoscopic surgery. We conducted this respective cohort study to compare the localization accuracy of two commonly used endoscopic marker strategies (endoscopic clip plus abdominal plain film and endoscopic tattooing). Methods: Patients who received preoperative colonoscopy localization for colonic neoplasia and underwent an elective laparoscopic operation afterward between 2013 and 2020 were included in this retrospective study. The localization accuracy of the two endoscopic strategies was compared, and the predictors of successful endoscopic localization were identified by multivariate regression. Results: In total, 195 patients [average age 62.4±9.2 years, 123 males (63.1%)] undergoing preoperative colonoscopy localization and subsequent laparoscopic colectomy for colonic neoplasms were included. Endoscopic localization was finally proven to be successful in 150 (76.9%) patients in the surgery. Compared to the tattooing group, patients who had successful localization for colonic lesions were fewer in the clip group (64 of 101 cases, 63.4% vs. 86 of 94 cases, 91.5%, P < 0.001). The multivariate regression analysis showed that the endoscopic tattooing strategy, endoscopic clip strategy, and lesion location were all predictors for successful localization (all with P < 0.001). Conclusion: Compared with endoscopic clip plus abdominal plain film, endoscopic tattooing had a higher localization accuracy and less intraoperative colonoscopy counseling; the endoscopic clip strategy, tattooing strategy and colonic lesion location were all predictors of successful endoscopic localization.